Planos de recursos hídricos de bacias hidrogr¡ficas: uma proposta de tipologia de ações e de indicadores para avaliação da sua implementação - Lima, Livia de Oliveira (2024)
The implementation of watershed management plans represents one of the main challenges in water resources management, and its evaluation plays a significant role in identifying strengths and areas for improvement of the plans. This study aims to enhance the assessment tools for the implementation of water resources plans through two contributions. Firstly, a typology of actions is proposed based on the analysis of seven watershed plans in the state of Cear·, where actions were categorized into first, second, and third-order types and subtypes. The analysis methodology involved the utilization of five watershed plans from S„o Paulo to verify the applicability of the typology and to include new subtypes not addressed in the plans from Cear·. The results presented 11 different categories of actions: structural, study, project, enforcement, monitoring, training, campaign, management, regulation, personnel expansion, and communication, with 96 distinct subtypes. Thus, the proposed typology proved adaptable to different watershed realities and applicable to other contexts of studies on water resources plans. The second study proposes the development and validation of indicators for plan evaluation based on the typology of actions. For this purpose, indicators were individually formulated for each existing subtype of action in the typology, with five metrics ranging from 0.0 to 1.0, considering the stages of action execution. Additionally, these indicators underwent a validation process by eight experts in the field of water resources, following the guidelines of the Delphi method. As a result, the indicators of all action categories were approved by the experts with an agreement rate exceeding 60%, requiring adjustments to the metrics based on relevant suggestions. It is concluded that the interconnection of indicators with the typology not only strengthens the evaluative structure but also contributes to a more comprehensive approach in the analysis of plan implementation.